COVID‐19 Modeling: High‐Resolution Agent‐Based Modeling of COVID‐19 Spreading in a Small Town (Adv. Theory Simul. 3/2021). Issue 3 (9th March 2021) - Truszkowska, Agnieszka; Behring, Brandon; Hasanyan, Jalil; Zino, Lorenzo; Butail, Sachit; Caroppo, Emanuele; Jiang, Zhong‐Ping; Rizzo, Alessandro; Porfiri, Maurizio
Abstract : Since 2020, COVID‐19 has wreaked havoc across the planet, taking the lives of more than one million people. The uncertainty and novelty of the current conditions call for the development of theory and simulation tools that can support effective policy‐making. In article number 2000277, Agnieszka Truszkowska, Maurizio Porfiri, and co‐workers report a high‐resolution, agent‐based modeling platform to simulate the spreading of COVID‐19 in the city of New Rochelle, NY—one of the first outbreaks registered in the United States. Image by Anna Sawulska, Agnieszka Truszkowska, Beata Truszkowska, and Maurizio Porfiri.